ผลของการลดอุณหภูมิแบบสุญญากาศและบรรจุภัณฑ์แอ็กทีฟต่อคุณภาพ ของผักกาดหอมตัดแต่งพร้อมบริโภค - กฤติยาณี วรรณภิระ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This research was aimed at studying the optimum process parameters for vacuum cooling and physico-chemical quality, pathogenic microorganism and storage life of vacuum cooled ready to eat crisp head, butter head and red coral lettuces that packed in different packaging. The optimum parameters of vacuum cooling for ready to eat crisp head, butter head and red coral lettuces were studied to obtain the final temperature of 4 ± 1 °C. In the experiment, three final pressures of 6.0, 6.5 and 7.0 millibar with holding times of 5 and 10 minutes were investigated. The results illustrated that the optimum parameters of 3 ready to eat lettuces were at the final pressure of 6.5 millibar with holding time of 5 minutes. The average overall cycle times of ready to eat crisp head lettuce were 18 minutes and the weight loss during vacuum cooling with the previous optimum parameters was 2.51 %. For ready to eat butter head lettuce the total cycle time was 19 minutes and the weight loss during vacuum cooling with the previous optimum parameters was 3.13 %. The total cycle time of ready to eat red coral lettuce was 19 minutes and the weight loss during vacuum cooling with the previous optimum parameters was 2.84 %. Subsequently, ready to eat lettuces from vacuum cooled and non-vacuum cooled were packed in 2 types of packaging: polypropylene bags (PP) and polyethylene bags (PE) in the ratio 1 : 1 : 1, then stored at 4 ± 1 °C. The results illustrated that vacuum cooled ready to eat lettuces had better appearance, lower weight loss, less total aerobic mesophilic bacteria and mold than nonvacuum cooled sample. Vacuum cooled ready to eat lettuces had storage life of 6 days which longer than non-vacuum cooled samples, which had storage life of 4 days. Ready to eat lettuces packed in PP bag had lower weight loss and less number of yeast than samples packed in PE. Ready to eat lettuces packed in PP bag had storage life of 6 days which longer than ready to eat lettuces packed in PE bag, which had storage life of 5 days. However, vacuum cooling and packaging had no effects on color, chlorophylls content, total soluble solids, titratable acidity, anthocyanin content, vitamin C content, antioxidant activity and phenolic compound of lettuces (p>0.05). In addition, the study on the effect of active packaging on quality changes of vacuum cooled ready to eat crisp head, butter head and red coral lettuces were determined. These vegetables were packed in PP and active packaging bags. Active packaging had different oxygen transmission, active bag EMA1 (oxygen transmission rate (OTR) = 10,000-12,000 ml/m2-day), EMA2 (OTR = 12,000-14,000 ml/m2-day) and EMA3 (OTR = 14,000-16,000 ml/m2-day). Subsequently, samples were stored at 4 ± 1 ºC. The results showed that after 7 days of storage, vacuum cooled samples packed in all active packaging bags had higher weight loss. The results showed that after 7 days of storage, vacuum cooled samples packed in all active packaging bags had higher weight loss percentage than samples packed in PP packaging. All EMA packaging contained higher oxygen content but lower carbon dioxide content than PP bag. Vacuum cooled ready to eat lettuces packed in active packaging type EMA2 had the best appearance score and could delay growth of aerobic mesophilic bacteria compared to the other type of packaging. Vegetables packed in EMA2 had the longest storage life of 10 days.